2014
DOI: 10.2105/ajph.2013.301658
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Care Seeking for Children With Pneumonia and Diarrhea in Guatemala: Implications for Intervention Strategies

Abstract: Proximal factors associated with recognizing need for care were important in determining formal care, and were strongly linked to social determinants. In addition to specific action by the health system with an enhanced community health worker role, a systems approach can help ensure barriers are addressed among poorer and more remote homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…Also, in our study we found a difference of illiteracy in maternal education between cases and controls (18.6% vs. 2.9%), a factor that has been shown to be associated with decreased likelihood to seek formal care for sick children, and which could be related to social group, distance from a health center, food intake, or mothers' behavior …”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Also, in our study we found a difference of illiteracy in maternal education between cases and controls (18.6% vs. 2.9%), a factor that has been shown to be associated with decreased likelihood to seek formal care for sick children, and which could be related to social group, distance from a health center, food intake, or mothers' behavior …”
Section: Discussionsupporting
confidence: 44%
“…Also, in our study we found a difference of illiteracy in maternal education between cases and controls (18.6% vs. 2.9%), a factor that has been shown to be associated with decreased likelihood to seek formal care for sick children, 37,38 and which could be related to social group, distance from a health center, food intake, or mothers' behavior. 39,40 It should be noted that vitamin D serum cutoffs that can prevent infections are still undefined. As a nonexperimental study, we could not control for confounding variables that we could not measure.…”
Section: Discussionmentioning
confidence: 99%
“…Only 43 percent of children with symptoms of acute respiratory infection in low-income countries were taken to a health care provider in the last decade [25]. Numerous studies show that distance from the nearest health facility is a significant barrier to seeking care for child illness, both because of the direct cost of travel and the indirect cost of time lost during travel [11,23,2628], which has led to initiatives to provide good-quality care in communities [29]. There is some evidence that improving accessibility to health care in low- and middle-income countries can improve health equity by reducing socioeconomic gaps in care [30].…”
Section: Introductionmentioning
confidence: 99%
“…Even in the public sector, medicines are often out of stock, and, thus, public providers may write prescriptions for patients to purchase medicines privately. Many health seekers eschew clinical providers altogether and directly seek care at pharmacies [37, 42–44]. In this setting, pharmacy staff may theoretically steer patients away from generics or “upsell” originator products.…”
Section: Introductionmentioning
confidence: 99%